TELAAH KRITIS PREDIKSI KREATIVITAS DAN KESUKSESAN AKADEMIS DENGAN METODE PENGUKURAN “FAKE PROOF” - Lina Anatan (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2013)
This paper discuss a critical review on the stud ywhich provides evidence that the relative-scored measure of the Big Five can help to limit the effects of biased responding. Students exposed to relatively simple instructions to fake good, as if simulating a job assessment situation, appeared able (1) to distort the factor structure of a standard Big Five personality measure; (2) to successfully present themselves in an enhanced manner, particularly exaggerating Conscientiousness and Emotional Stability, the two best personality predictors of job performance; and (3) to reduce the relationship between standard Big Five measures and two measures of performance (CGPA and CAQ) to insignificance. This suggests that the relative measures might be used to investigate the structure of implicit or explicit models of expected ideal behaviour, in different situations of administrator or target demand. In consequence, we are currently investigating self-presentation using relative measures in other stressful and competitive situations that are not specifically job performance relatedKeywords: creativity, academic performance. Fake proof, the big five personality